Increased brain age in adults with Prader-Willi syndrome - Azor,AM; Cole,JH; Holland,AJ; Dumba,M; Patel,MC; Sadlon,A; Goldstone,AP; Manning,KE (NeuroImage: Clinical, 2019)
Prader-Willi syndrome (PWS) is the most common genetic obesity syndrome, with associated learning difficulties, neuroendocrine deficits, and behavioural and psychiatric problems. As the life expectancy of individuals with PWS increases, there is concern that alterations in brain structure associated with the syndrome, as a direct result of absent expression of PWS genes, and its metabolic complications and hormonal deficits, might cause early onset of physiological and brain aging. In this study, a machine learning approach was used to predict brain age based on grey matter (GM) and white matter (WM) maps derived from structural neuroimaging data using T1-weighted magnetic resonance imaging (MRI) scans. Brain-predicted age difference (brain-PAD) scores, calculated as the difference between chronological age and brain-predicted age, are designed to reflect deviations from healthy brain aging, with higher brain-PAD scores indicating premature aging. Two separate adult cohorts underwent brain-predicted age calculation. The main cohort consisted of adults with PWS (n=20; age mean 23.1years, range 19.8-27.7; 70.0% male; body mass index (BMI) mean 30.1kg/m2, 21.5-47.7; n=19 paternal chromosome 15q11-13 deletion) and age- and sex-matched controls (n=40; age 22.9years, 19.6-29.0; 65.0% male; BMI 24.1kg/m2, 19.2-34.2) adults (BMI PWS vs. control P=.002). Brain-PAD was significantly greater in PWS than controls (effect size mean±SEM +7.24±2.20years [95% CI 2.83, 11.63], P=.002). Brain-PAD remained significantly greater in PWS than controls when restricting analysis to a sub-cohort matched for BMI consisting of n=15 with PWS with BMI range 21.5-33.7kg/m2, and n=29 controls with BMI 21.7-34.2kg/m2 (effect size +5.51±2.56years [95% CI 3.44, 10.38], P=.037). In the PWS group, brain-PAD scores were not associated with intelligence quotient (IQ), use of hormonal and psychotropic medications, nor severity of repetitive or disruptive